(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Albee’s work also demands a separation - separation from masked innocence in order to experience reality. Art, for Albee, is a medium to make man confront reality, and this reality can never be embraced without accepting the final reality of his life i.e., death. Albee’s theater has portrayed a number of instances and circumstances in order to make us strong enough to accept the ultimate separation from ‘life at death.’ Pleasure and pain, success and failure, life and death make up two sides of a coin. Only one side is visible at one time but the other side is also waiting for its turn, this is what Albee advocates. An important part of this acceptance is this that the person who has taken birth is bound to die as well. Robert Rowland Smith has rightly asserted that, “Everything that lives, dies . . . . Rather than being opposites, therefore, it’s fairer to say that living and dying depend on each other, each the other’s condition” (01). Thus, if one has taken birth, his death is certain as well. But man forgets this certainty and starts expecting too much from life – power, possession, love, companions, happiness – as if he will remain in this state forever. Forgetting that inevitability of death is also a ‘Life-Lie’ as it leads to plan so much which is nothing but an illusion. The reality is this nothing belongs to man as he is only a traveler and can never attain stable position or state in the journey named life.